Re-establishing the concept of free trade due to climate change : particularly in the light of the WTO provisions and carbon tariffs - Mäntymaa, Eemi (My University, 2020)
This thesis examines the compatibility of carbon tariffs that may be used in climate change mitigation with existing World Trade Organization (WTO) provisions. If a state or international entity, such as the European Union, decides to restrict international free trade on the basis of climate, it will challenge the well-established global free trade consensus, which is most strongly represented by the WTO and its provisions. For this reason, the perspective of the thesis is the clash between climate law, which has emerged from the field of international environmental law, and international free trade. The main research question relates to the compatibility of carbon tariffs with WTO provisions. The imposing of carbon tariffs is examined in particular in the light of the principle of national treatment and the most-favored nation clause. Additionally, the thesis assesses whether a climate-based restriction on free trade could be justified under GATT Article XX on general exceptions. Furthermore, the thesis investigates the emergence of climate law and its characteristic features, as well as carbon tariffs as a part of its judicial instruments. Finally, the thesis examines the positions of the international free trade tradition and the concept of the sustainable economy in the new millennium. Climate actions can be implemented through the use of regulatory or economic instruments, or so-called soft law. According to the Paris Agreement, the rise in global average temperature should be restrained well below two degrees. For example, the EU seeks to meet these obligations through its set of policy initiatives, known as the European Green Deal, which includes, on the one hand, the goal of moving towards a sustainable economy and, on the other hand, the possibility of imposing carbon tariffs. Thus, the imposing of carbon tariffs is also linked to the wider debate on the role of international free trade and globalization. The conclusion of the thesis is that the existing WTO provisions would allow carbon tariffs to be imposed. In addition, when choosing appropriate policy instruments, the international community must also take into account aspects related to justice and a sense of fairness. The standing of institutionalism, as well as general trends such as populism and protectionism, influences policy choices. The thesis mainly utilizes legal dogmatics, especially in the section on the interpretation of WTO provisions. The thesis also includes research on policy instruments and the application of the hermeneutic method. The source material consists of legal literature, WTO case law, political discourse, and research findings by other scholars.

Tässä tutkielmassa tarkastellaan ilmastonmuutoksen vastaisessa toiminnassa mahdollisesti käytettävien hiilitariffien yhdenmukaisuutta olemassa olevien Maailman kauppajärjestön (WTO) säännösten kanssa. Jos jokin valtio tai kansainvälinen entiteetti, esimerkiksi Euroopan unioni, päättää rajoittaa kansainvälistä vapaakauppaa ilmastoperusteisesti, haastaa se asemansa vakiinnuttaneen globaalin vapaakauppakonsensuksen, jota WTO ja sen eri säännökset vahvimmin edustavat. Tästä syystä tutkielman näkökulmana on merkitystään kasvattaneen ja kansainvälisestä ympäristöoikeudesta eriytyneen ilmasto-oikeuden ja kansainvälisen vapaakaupan yhteentörmäys. Varsinainen tutkimuskysymys liittyy hiilitariffien yhteensopivuuteen WTO -säännösten kanssa. Hiilitariffien asettamista tarkastellaan erityisesti kansallisen kohtelun periaatteen ja suosituimman maan kohtelua koskevan lausekkeen valossa. Lisäksi tutkielmassa kartoitetaan, voisiko ilmastoperusteista vapaakaupan rajoittamista perustella yleisiä poikkeuksia koskevalla GATT artiklalla XX. Edelleen tutkielmassa tarkastellaan ilmasto-oikeuden syntyä ja sen luonteenomaisia piirteitä sekä hiilitariffeja osana sen ohjauskeinovalikoimaa. Lopuksi tutkielma pohtii kansainvälisen vapaakauppatradition ja uuden, kestävää taloutta koskevan konseptin asemaa uudella vuosituhannella. Pariisin sopimuksen mukaan maapallon keskilämpötilan nousu tulisi pidättää selvästi alle kahdessa asteessa. Esimerkiksi tähän velvoitteeseen EU pyrkii vastaamaan vihreän kasvun ohjelmallaan (European Green Deal), johon sisältyy toisaalta tavoite kestävään talouteen siirtymisestä ja toisaalta mahdollisuus hiilitariffien asettamiseen. Siten hiilitariffien asettaminen liittyy myös keskusteluun kansainvälisen vapaakaupan ja globalisaation asemasta. Tutkielman johtopäätös on se, että WTO:n olemassa olevat säännöt mahdollistaisivat hiilitariffien asettamisen. Lisäksi sopivia ohjauskeinoja valittaessa kansainvälisen yhteisön on huomiotava oikeudenmukaisuuteen liittyvät näkökohdat. Institutionalismin yleinen asema sekä populismin ja protektionismin kaltaiset suuntaukset vaikuttavat valittaviin politiikkatoimiin. Tutkielma hyödyntää pääosin lainopillista metodia erityisesti WTO -säännösten tulkintaa koskevassa osiossa. Tämän lisäksi tutkielma sisältää ohjauskeinotutkimusta sekä hermeneuttisen metodin soveltamista. Lähdeaineisto koostuu lainopillisesta kirjallisuudesta, WTO:n oikeuskäytännöstä, poliittisista diskursseista ja muista akateemisen yhteisön tutkimustuloksista.
Keywords: climate law, carbon tariffs, international free trade, restrictions on free trade, World Trade Organization, globalization, sustainable economy